High country fall eaudiobook Deborah knott mysteries series, book 10. - Maron, Margaret (Judge Deborah Knott, 2005)
Publishers Weekly declares that the "leaves of autumn are in full splendor, and so is Maron's talent in her 10th Deborah Knott adventure." Judge Knott is finally ready to marry her long-time friend Deputy Sheriff Dwight Bryant and settle down-or is she? She jumps at a chance to fill in for a judge in the high country of North Carolina. But ugly murder haunts the beauty of the Smoky Mountains.